Impact of YouTube Tutorials in Skill Development among University Students of Lahore: Moneeba Iftikhar * Sohail Riaz ** Zahid Yousaf*** (PJDOL, 2023)
YouTube is becoming part of popular culture. To explore this advanced advent of technology in learning prospect, this study aims at finding the popularity of the YouTube tutorials among youth, along with their dependency on these videos and their usefulness. The focus of this research paper is on learning skills by watching YouTube tutorial among university students of Lahore, Pakistan. Software learning skills development has been analyzed among the students of 18-22 years. The respondents of the study were students of leading universities of Lahore.